2018
DOI: 10.1039/c7cc07790d
|View full text |Cite
|
Sign up to set email alerts
|

Highly-luminescent Eu,Sm,Mn-doped CaS up/down conversion nano-particles: application to ultra-sensitive latent fingerprint detection and in vivo bioimaging

Abstract: Due to their unique properties, rare-earth doped upconversion luminescence (UCL) nanomaterials are of considerable scientific interest. Meanwhile, alkaline-earth sulfide materials based on a completely different electron trapping (ET) mechanism demonstrate extremely high UCL efficiencies, which are several dozens of times more than those of conventional fluoride UCL nanomaterials. However, the large particle size, easy hydrolysis, and difficulty in achieving uniform dispersion have precluded bioassay applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Very recently, Wang et al reported interesting nanoparticles, CaS:Eu 2+ ,Sm 3+ ,Mn 2+ , that show strong red emission from the Eu 2+ 5d→4f transition, and that are able to generate highly visible fingerprint images compared to conventional NaYF 4 :Yb,Er,Mn UCNPs . The trap centers of the tri‐doped CaS nanoparticles store the absorbed energy from initial UV/visible irradiation and release the photon energy when the traps are excited by NIR light.…”
Section: Forensic Applicationsmentioning
confidence: 99%
“…Very recently, Wang et al reported interesting nanoparticles, CaS:Eu 2+ ,Sm 3+ ,Mn 2+ , that show strong red emission from the Eu 2+ 5d→4f transition, and that are able to generate highly visible fingerprint images compared to conventional NaYF 4 :Yb,Er,Mn UCNPs . The trap centers of the tri‐doped CaS nanoparticles store the absorbed energy from initial UV/visible irradiation and release the photon energy when the traps are excited by NIR light.…”
Section: Forensic Applicationsmentioning
confidence: 99%
“…[21][22][23][24][25] The feature of anti-Stokes photon upconversion of PSL NCs, along with the high tissue penetration depth and the absence of autouorescence in biological specimens under NIR stimulation, makes them extremely suitable for use as sensitive luminescent nanoprobes for various bioapplications. [26][27][28][29][30] Rare earth (RE) doped alkaline-earth suldes (AES), as famous electron-trapping materials, have shown great promise in many technological elds because of their excellent cathodoluminescence, electroluminescence, photoluminescence (PL), PersL, and PSL properties. [31][32][33] Specically, RE-doped CaS NCs such as CaS:Eu 2+ ,Dy 3+ and CaS:Eu 2+ ,Sm 3+ ,Mn 2 are regarded as promising PSL nanoprobes for in vitro biodetection and in vivo bioimaging owing to their superior PSL characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] Specically, RE-doped CaS NCs such as CaS:Eu 2+ ,Dy 3+ and CaS:Eu 2+ ,Sm 3+ ,Mn 2 are regarded as promising PSL nanoprobes for in vitro biodetection and in vivo bioimaging owing to their superior PSL characteristics. 28,29 However, currently the controlled synthesis of highly efficient RE-doped CaS PSL NCs with a broad NIR response range and ultralow stimulation power density threshold remains notoriously difficult. A systematic investigation of RE-doped CaS PSL NCs from the controlled synthesis, fundamental PSL photophysics to bioapplications, which is of vital importance for their optical performance optimization and for future design of efficient PSL nanoprobes, remains unexplored so far.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al synthesized CaS:Eu,Sm,Mn and functionalized them with 1‐dodecanethiol and 11‐mercaptoundecanoic acid (DT/MUA@ESMCaS) to use for fingermark detection (J. Wang et al, ). They compared the results with NaYF 4 :Yb,Er,Mn functionalized with 3‐mercaptopropionic acid (MPA‐NaYF 4 ).…”
Section: Upconvertersmentioning
confidence: 99%